A Critical Review on Paul Schrader’s Book Transcendental Style in Cinema Ozo, Bresson, Dreyer - Mohammadjavad Goharbakhsh; Shahab Esfandiari; Pedram Rostami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
"Transcendental Style in Cinema, Ozu, Bresson, Dreyer" by Paul Schrader, the famous American critic, writer, and director, is one of the few books that explores the relationship between cinema, religion, and related elements beyond various fields such as Semiotics. This book was translated in 2003 by Mohammad Gozarabadi in Iran. The second edition of the book that was published in 2018 included the introduction of slow cinema and Schrader's revision of some of the concepts of this style. The importance of this book could be seen in the method of studying and confronting religion and its elements. Using profound philosophical concepts and Christian background, Schrader establishes stylistic stages in which the most important movies could be read and analyzed through them. This style aims to discover the state in which the transcendental and spiritual manner is expressed in cinema. Therefore, firstly the book and the author are introduced and then by considering both editions, all the concepts in the book are discussed and finally the book is criticized from different aspects. The results will demonstrate that the main criticisms on this book can be seen in the levels of method and content.